Formação de classes de equivalência de estímulos em idosos: revisão sistemática e desenvolvimento de um teste cognitivo digital breve - Nery, Andreza Gomes Spiller (2021)
There is a rapid and significant increase in relation to population aging associated with the high prevalence of chronic diseases, including dementia. In this sense, it is important that brief screening instruments are available to assess the cognitive decline of the elderly. In addition to traditional tests, performed with paper and pen, digital tests can currently be used, which would increase the availability and scope of tests to assess the cognitive functioning of the elderly. In this context, this dissertation proposes a brief digital cognitive test based on a task of training equivalence classes in the elderly and reviews the published studies on the formation of equivalence classes in the elderly. Objective: Two studies have been conducted with the following objectives: 1) conduct a systematic review of studies that evaluated the formation of stimulus equivalence classes in the elderly; 2) propose a brief digital cognitive test based on the stimulus equivalence paradigm. Methods: For the first study, a search was conducted with the following keywords: (equivalence class formation OR stimulus equivalence OR equivalence classes) AND (elderly OR older adults). The databases used were Pubmed, PsycInfo, Web of Science, Scopus, Scielo and Biblioteca Virtual em Saúde. In total, 457 articles were found. After the exclusion of the articles according to the exclusion criteria, 11 articles were selected for the present review. In the second study, 50 elderly people were evaluated, who were later divided into groups with and without cognitive decline. The elderly were evaluated using the Digital Test, Mini-Mental State Examination (MMSE), Brief Cognitive Battery (BCB) and Five Digits Test (FDT). Results: Based on the systematic review, the results found indicate that the procedures based on the stimulus equivalence paradigm enable the learning of the elderly. Also can be verified the importance of some elements in the formation of classes, such as: types of stimuli and arrangements used, class size, presence of pre-training, type of training and feedback and consequences provided to the participant. Regarding the second study, the results indicate that the majority of correlations between the variables of the brief digital cognitive test and the scores of traditional cognitive tests were statistically significant. In addition, there were significant differences between the scores of elderly with and without cognitive decline. Conclusions: The paradigm of stimulus equivalence enables the learning of the elderly. In addition, the characteristics of the procedures may influence the emergence of equivalence classes. The brief digital cognitive test based on the stimulus equivalence paradigm can be a valid instrument for cognition assessment in the elderly.